Both J- and L-shaped upper hemisternotomy approaches are suitable for total arch replacement with frozen elephant trunk in patients with Type A dissection - Yang, Zhonglu; Jiang, Hui; Liu, Yu; Ge, Yuguang; Wang, Huishan (Frontiers in Cardiovascular Medicine, 2022)
Background: Minimally invasive total arch replacement (TAR) with frozen elephant trunk (FET) implantation can be carried out through J-, L-, and inverted T-shaped upper ministernotomy. L- and inverted T-shaped upper ministernotomy are selected mostly for their better surgical view compared to J-shaped. However, few studies have paid attention to the difference in clinical effects between J- and L-shaped upper hemisternotomy in acute Type A aortic dissection (ATAAD). Methods: We retrospectively analyzed 74 consecutive patients with ATAAD who underwent TAR with FET implantation between December 2019 and October 2020. Patients were divided into the L group (n = 31, L-shaped upper hemisternotomy) and the J group (n = 43, J-shaped upper hemisternotomy). Perioperative characteristics were recorded. Results: No significant difference was found in any of the preoperative, postoperative, or follow-up variables between the two groups. However, the CPB establishment time in the J group was significantly shorter than that in the L group (65.0±17.9 min vs. 77.9±17.2 min, P < 0.05). Other intraoperative variables showed no significant difference. Conclusions: TAR with FET implantation is feasible and can be carried out safely via J-shaped or L-shaped incision. A J-shaped incision might be beneficial for single incisions, while an L-shaped incision might be beneficial if an extra incision is required to achieve better artery perfusion.